Improving the quality of graphene oxide prepared by Hummer's method by using centrifugation - Ardakani, S.E.M. (American Institute of Physics Inc., 2015)
Hummer's method is one of the most popular methods for preparing graphene oxide. This method requires fewer hazardous materials and is carried out at lower temperatures. The graphene oxide sheets prepared by this approach, contains various functional groups such as epoxide and hydroxyl. The oxidation of graphite by powerful oxidants used in this method is not easily controllable and this causes the quality exfoliated sheets to vary. Furthermore, reducing the PH of the solution and washing the sample in the final stage of process by filtration cannot separate the nanosheets. Hence, in this study, washing of the samples by distilled water in the filtration setup was replaced by centrifuge approach. The microscopic characterizations like TEM, FESEM, SAED and EDX that were carried out revealed that centrifuging the samples gave better outcomes for the Hummer's method. Â© 2015 AIP Publishing LLC.